Monitoring of Economy Activity Financing Process - Kanapėnaitė-Mažintienė, Aurelija (Ekonomika, 1998)
This article analyses the process of financing the economy activity. Monitoring of the process is considered as a main problem, and suggested solution to it is consideration of financial needs of financing process participants (both financing and financed). Lithuanian financing process was analysed through informational materials on credit flows, provided by various governmental institutions.